2000
DOI: 10.1089/088922200309025
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Note: Identification of All HIV Type 1 Group M Subtypes in Senegal, a Country with Low and Stable Seroprevalence

Abstract: A total of 343 HIV-1-positive samples obtained between June 1996 and March 1999 was genetically characterized in the envelope region by HMA and/or sequencing. The env subtype distribution was as follows: 290 (84.6%) A, 22 (6.5%) B, 16 (4.7%) C, 8 (2.5%) D, 1 (0.03%) E, 1 (0.03%) F1, 4 (1.2%) G, and 1 (0.03%) H. For 77 samples the p24 region from the gag gene was also sequenced, and for 9 (11.6%) the subtypes between env and gag were different. Phylogenetic tree analysis showed the predominance of AG-IBNG-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
31
2
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 25 publications
5
31
2
1
Order By: Relevance
“…Indeed, in western Africa, 80% of the subtype A samples can be detected with the specific subtype A primers (42), and HMA was able to identify the genetic subtype for more than 90% of the samples (43,58). In the DRC, only 45% of the subtype A samples could be detected with the subtype A-specific primers, and less than 50% could be identified by HMA.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in western Africa, 80% of the subtype A samples can be detected with the specific subtype A primers (42), and HMA was able to identify the genetic subtype for more than 90% of the samples (43,58). In the DRC, only 45% of the subtype A samples could be detected with the subtype A-specific primers, and less than 50% could be identified by HMA.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of HIV-1 infections in sub-Saharan Africa are caused by subtypes A and C (30). The HIV-1 subtype A epidemic, including CRF02_AG-IbNg-like strains (20,21,35,55,70,75,77,79,102,108), dominates in West, Central, and East Africa and reached a plateau at the prevalence rate of 1.5 to 14% by the 1990s (111,112). In contrast, countries in southern Africa and the horn of Africa have experienced the greatest burden of the AIDS epidemic caused predominantly by HIV-1 subtype C (HIV-1C).…”
mentioning
confidence: 99%
“…HIV-1 infection in West Africa is principally due to CRF02AG (2,4,6,19,22,23,25). Recent work conducted in our laboratory revealed that a distinct group of viruses within the HIV-1A subtype radiation is also present in Senegal (30,32,35). Phylogenetic analyses indicated that this group of viruses, which we previously referred to as HIV-1A subcluster 2, differed from sub-subtypes A1 and A2 (30,32).…”
mentioning
confidence: 73%